2017
DOI: 10.1016/j.jpubeco.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Location-based tax incentives: Evidence from India

Abstract: This paper studies the impact of the Government of India financed "New Industrial Policy for Uttarakhand and Himachal Pradesh", whereby beginning 2003, new industrial units and existing units upon expansion were given 100% income tax and excise tax exemption. Using a difference-indifferences approach, I find a large increase in employment, number of factories, total output and fixed capital at the 3-digit industry level. Using firm level data, I find that the average employment, output, fixed capital, and addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 35 publications
0
60
0
4
Order By: Relevance
“…Similarly, the central government implemented a tax incentive and capital subsidy scheme in 2003 in two relatively under‐industrialized states (Himachal Pradesh and Uttarakhand). Applying a difference‐in‐differences approach, Chaurey () finds that the policy resulted in large increases in outcomes such as employment, number of firms, and total output in the treatment states relative to the control states.…”
Section: Policy Implications and Discussionmentioning
confidence: 99%
“…Similarly, the central government implemented a tax incentive and capital subsidy scheme in 2003 in two relatively under‐industrialized states (Himachal Pradesh and Uttarakhand). Applying a difference‐in‐differences approach, Chaurey () finds that the policy resulted in large increases in outcomes such as employment, number of firms, and total output in the treatment states relative to the control states.…”
Section: Policy Implications and Discussionmentioning
confidence: 99%
“…Similarly, districts of Group 3 did not adversely affect neighboring districts of Group 5 and Group 6. This may explain in part why Chaurey (2016) does not find any spatial spillovers when he assessed India's New Industrial Policy. Himachal Pradesh, one of the two states covered by the policy, was designated a backward state in 1993 and its neighboring state Punjab had all districts from Group 6.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the impact of the special economic zones program in the PRC, Wang (2013) found that these zones increased the level of foreign direct investment and exports as well as average wages of workers in the host municipalities and generated a moderate displacement effect in the adjacent municipalities. Closer to our paper is Chaurey (2016), which examines the New Industrial Policy of India's federal government that offered tax exemptions and capital subsidies for firms in two states, Uttarakhand and Himachal Pradesh, since 2003. Applying a difference-in-differences approach, the author showed that the policy resulted in large increases in outcomes such as employment, number of firms, and total output in the treatment states relative to the control states.…”
mentioning
confidence: 99%
“…The Synthetic Control Method (SCM) invented by Abadie and Gardeazabal (2003) and further developed by Abadie et al (2010) and Abadie et al (2015) is a unique technique for investigating the specific effects of a particular social shock or institutional change. Government policy is a common shock so following Abadie et al (2010) more recent research such as Marcus and Siedler (2015) and Chaurey (2016) continues to employ the SCM to evaluate the effect of a wide variety of government policies. The SCM works by calculating a synthetic counterfactual which could not happen and has not happened in the real world.…”
Section: Synthetic Control Methodsmentioning
confidence: 99%